Illness perceptions, self-care practices, and glycemic control among type 2 diabetes patients in Chiang Mai, Thailand - Ngetich, E; Pateekhum, C; Hashmi, A; Nadal, IP; Pinyopornpanish, K; English, M; Quansri, O; Wichit, N; Kinra, S; Angkurawaranon, C (BioMed Central, 2022)
Background: Diabetes Self-Management Education (DSME) is a fundamental aspect of diabetes care, but no standard program exists in Thailand. Understanding current patterns of illness perceptions (concerns) and self-management practices among patients with diabetes in Thailand is vital to develop culturally tailored DSME programs. This study sought to explore the association between reported self-management practices and diabetes perceptions on glycemic control among patients with type 2 diabetes in Chiang Mai Province, Thailand. Specifically, the study examined whether the association between illness perceptions and diabetes control was mediated by self-management.